Validated Reverse Phase HPLC Method for the Determination of DEHP Content in Reconstituting Diluents and in Reconstituted Solutions of Imipenem and Cilastatin for Injection - A. K. Chaudhary; S. Ankushrao Waske; S. Yadav; T. G. Chandrashekhar; Vandana Singh (E-Journal of Chemistry)
A simple, rapid, accurate and economic reverse phase HPLC method was developed and validated for determination of di-(2-ethylhexyl)phthalate (DEHP) in reconstituting diluents and reconstituted solutions of imipenem and cilastatin for injection The method was applied to detect any leaching enhancement in presence of imipenem and cilastatin in reconstituted injections. Imipenem and cilastatin for injection is a widely used broad spectrum beta-lactam antibiotic. As per requirements of various regulatory authorities of different countries, DEHP content needs to be monitored in the reconstituting diluents used to reconstitute injections. The proposed method is a unique method wherein DEHP can be determined directly without any sample pre-treatment before analysis. The method can be used as a good quality control tool to control the leaching of DEHP in the reconstituting diluents and reconstituted injections. The method utilizes C18 column (250 × 4.6 mm, 5μ) and a mixture of methanol, propan-2-ol and water as mobile phase. DEHP was detected at 225 nm. The method has low limit of quantification (0.058 μg mL-1) which is much below the acceptance limit calculated as per USFDA tolerance criteria (3.5 μg mL-1 for adults and 0.3 μg mL-1 for neonates and infants).